Equally high prevalences of infection with cagA-positive Helicobacter pylori in Chinese patients with peptic ulcer disease and those with chronic gastritis-associated dyspepsia. - Pan, Z J (1997)
Approximately 60% of Helicobacter pylori isolates in the Western world possess the cytotoxin-associated gene A (cagA). cagA-positive H. pylori is found to be associated with peptic ulcer disease (PUD) and gastric adenocarcinoma. To investigate the cagA status of H. pylori isolates from Chinese patients with PUD and chronic gastritis (CG), H. pylori populations from 83 patients, 48 with PUD and 35 with CG, were assessed by two different cagA-specific PCRs, Southern blotting, and colony hybridization. The combined results from PCR, Southern blotting, and colony hybridization indicate a prevalence of cagA-positive H. pylori isolates of 98% (47 of 48) among Chinese PUD patients and 100% (35 of 35) among Chinese CG patients. Amplification with primer sets 1 and 2 yielded 52 and 95% of the 82 cagA-positive Chinese H. pylori, respectively. In contrast, the sensitivity of cagA-specific PCR for cagA-positive H. pylori isolates from Dutch patients with primer set 1 was 92% (112 of 122) and that with primer set 2 was 91% (50 of 55). The prevalence of cagA-positive H. pylori populations in Chinese patients with PUD and CG is almost universally high. Therefore, cagA cannot be used as a marker for the presence of PUD in Chinese patients. Our data further suggest that allelic variation in cagA may exist and that distinct H. pylori genotypes may circulate in China and Western Europe.